A new medium for the detection of gelatin-hydrolyzing activity of human dental plaque flora. - Syed, S A (1976)
A new medium for the detection of gelatin-hydrolyzing activity of human dental plaque flora by a simplified plate method is described. It is designed to support the growth of obligate anaerobes, facultative anaerobes, and aerobes. This medium can be used for the identification of gelatinase-producing organisms of clinical importance.